2006
DOI: 10.3748/wjg.v12.i32.5122
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion transmitted virus: A review on its molecular characteristics and role in medicine

Abstract: The present review gives an updated overview of transfusion transmitted virus (TTV), a novel agent, in relation to its molecular characteristics, epidemiological features, modes of transmission, tissue tropism, pathogenesis, role in various diseases and its eradication from the body. TTV, a DNA virus, is a single stranded, non-enveloped, 3.8 kb long DNA virus with a small and covalently closed circular genome comprising 3852 bases. It was tentatively designated Circinoviridae virus.TTV genome sequence is heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 163 publications
3
19
1
Order By: Relevance
“…In the present study, prevalence of TTV and HGV co-infections with HCV infection among thalassemic subjects were found to be comparable to that reported in studies from India (Panigrahi, Saxena, Acharya & Panda, 1998;Asim, Potukuchi, Arora, Singh & Kar, 2008). Several studies based on liver enzyme profile concluded that neither HGV nor TTV has any pathogenic role in liver damage (Sampeitro et al,1997;Irshad, Joshi, Sharma & Dhar 2006;Matsumoto et al,1999). However few studies have postulated a beneficial role of HGV co-infection in the pathogenesis of HIV infections, based on study of liver enzyme profile, short term clinical observation and have included HIV/HGV co-infected patients as study subjects (Feng et al, 2014;Stapleton, Williams & Xiang, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, prevalence of TTV and HGV co-infections with HCV infection among thalassemic subjects were found to be comparable to that reported in studies from India (Panigrahi, Saxena, Acharya & Panda, 1998;Asim, Potukuchi, Arora, Singh & Kar, 2008). Several studies based on liver enzyme profile concluded that neither HGV nor TTV has any pathogenic role in liver damage (Sampeitro et al,1997;Irshad, Joshi, Sharma & Dhar 2006;Matsumoto et al,1999). However few studies have postulated a beneficial role of HGV co-infection in the pathogenesis of HIV infections, based on study of liver enzyme profile, short term clinical observation and have included HIV/HGV co-infected patients as study subjects (Feng et al, 2014;Stapleton, Williams & Xiang, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…TTV was first characterized as a blood-born virus and thus referred to transfusion-transmitted (TT) group of viruses [ 1 ]. Recent studies suggested the existence of other ways of transmission including parenteral [ 3 ], sexual [ 9 , 10 ], mother-to-child [ 11 , 12 ] and others [ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of recent study was to survey the rate of infection of TTV in the Jahrom, Southern of Iran. TTV was first originally isolated from a patient with fulminant hepatitis in Japan in 1997 by Nishizawa and also from chronic liver disease of unknown etiology and cryptogenic hepatitis (19). These findings assumed that TTV may associate with hepatitis, although to date a causative effect has not been established (20).…”
Section: Discussionmentioning
confidence: 99%
“…These findings assumed that TTV may associate with hepatitis, although to date a causative effect has not been established (20). TTV has been found to be extremely common in humans with high worldwide prevalence, patients with a broad spectrum of hepatic disorders concomitant with HBV or HCV (19,21) as well as in healthy people that is very variable, and also in order to clear pathology of TTV infection, further studies should be performed to evaluate prevalence of TTV infection in region patients. According to the result of this study, the prevalence of TTV in patients with chronic HBV and HCV in the southern of Iran was 50.8 and 66.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%